BUDIDAYA SELADA ORGANIK DI KAWASAN RUMAH PANGAN LESTARI DARI KWT PANORAMA SEBAGAI BENTUK NYATA KEGIATAN EKONOMI PRODUKTIF - Nurlianti Nurlianti; Prihanani Prihanani (DHARMA RAFLESIA, 2018)
The concept of Sustainable Food House (KRPL) is a farming concept that mobilizes farmer groups to provide daily food needs or produce it for market. Partner Group Two is a group of Panorama women farmers who have succeeded in running KRPL but in observation of Unihaz Service Team of Panorama women farmer group which is implementing this program still use conventional farming concept by using chemical fertilizer. The results of the devotion program has provided an understanding of the importance of organic cultivation, especially Lettuce plant and then followed by cultivation of organic lettuce cultivation by using bokhasi organic fertilizer from Mitra One. One partner group is a group of women farmers who live in oil palm plantations and since 2014 has been accompanied to become producers of agricultural waste bokhasi of rural chicken waste and palm plantation waste. Both agricultural wastes, which is the main raw material for making bokhasi, is available sustainably in their area of residence, so it can become a business opportunity. The dedication program that has been implemented is the consolidation program as a producer of bokhasi, packaging improvement, bokhasi product sales, bokhasi house improvement and KRPL concept adobsi from partner two. The purpose of IbM program for Mitra Satu has been successfully supplied bokhasi especially to partner two and can adopt KRPL technology which has been implemented by Mita Dua. The objective of IbM program for Mitra Dua has been to successfully carry out organic cultivation on vegetable crops, especially organic slaves that are environmentally friendly and healthier for consumers. The ultimate goal of both programs is to successfully produce healthy organic farm products for consumers by utilizing agricultural waste into the main raw material of bokhasi so that it becomes a productive economic business opportunity for both partners. Keywords: organic cultivation, bokhasi, KRPL, productive economy